6d+(5.5)=2d-(6.5)

Simple and best practice solution for 6d+(5.5)=2d-(6.5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6d+(5.5)=2d-(6.5) equation:


Simplifying
6d + (5.5) = 2d + -1(6.5)
6d + 5.5 = 2d + -1(6.5)

Reorder the terms:
5.5 + 6d = 2d + -1(6.5)

Multiply -1 * 6.5
5.5 + 6d = 2d + -6.5

Reorder the terms:
5.5 + 6d = -6.5 + 2d

Solving
5.5 + 6d = -6.5 + 2d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-2d' to each side of the equation.
5.5 + 6d + -2d = -6.5 + 2d + -2d

Combine like terms: 6d + -2d = 4d
5.5 + 4d = -6.5 + 2d + -2d

Combine like terms: 2d + -2d = 0
5.5 + 4d = -6.5 + 0
5.5 + 4d = -6.5

Add '-5.5' to each side of the equation.
5.5 + -5.5 + 4d = -6.5 + -5.5

Combine like terms: 5.5 + -5.5 = 0.0
0.0 + 4d = -6.5 + -5.5
4d = -6.5 + -5.5

Combine like terms: -6.5 + -5.5 = -12
4d = -12

Divide each side by '4'.
d = -3

Simplifying
d = -3

See similar equations:

| 6d+5.5=2d-(6.5) | | 6d+5.5=2d-6.5 | | 17x+3=17x | | -33*1/5 | | 288/6 | | (3/4)-(9/12) | | 68(x-3)=-2x+35.6 | | 10x+5y+15z= | | (x-1)(x+5)-(x+2)(x-3)=3(1+5x) | | -8x-18=6 | | (3/4)-(3/12)= | | y-21=2(x-9) | | m-8-2=4 | | TanX=27/32 | | 3/4-3/12 | | 5(3x-1)+7=2-(5x-3) | | F(x)=4x^2+7x-6 | | 5(2x+1)=3x+19 | | -7x^2+34x+5= | | x+2(80-x)=100-4(25-x) | | 6x/(x^2) | | g^2+4g-32=9 | | 5x=6x-14+12 | | y/7=2/x | | 84/(7) | | 9x/4=15 | | 9x/4=`15 | | 3x+5(2x-12)=5 | | 4x+3y=z | | 8+5x=7x+2 | | -2+10x=8x+1 | | -6*x=36 |

Equations solver categories